PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Ibnu Imam Al Ayyubi; Erwan Nudin; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is motivated by the low ability of mathematical problem solving of high school students who need a learning approach to overcome the problem. Alternative approach used is problem-based learning approach. This study aims to examine whether the problem-solving ability of mathematical students using problem-based learning is better than using ordinary learning. The research method used is experimental method. At the end of the learning the two classes were given a test. The population in this study were high school students in SMAN 2 Cimalaka class XI, while the sample consisted of two classes chosen at random. The data collection in this research is a test of five questions, then the scores of mathematical problem solving abilities are analyzed by descriptive statistics and inferential statistic using two difference test average. Based on the results of research, both from data analysis and hypothesis testing, the authors conclude that the problem solving ability of mathematical students using problem-based learning is better than using ordinary learning.